Primary Renal Embryonal Rhabdomyosarcoma in Adults: A Case Report and Review of the Literature - Rafik Nabil Fanous; Erik K. Mayer; Justin Vale; Josephine Lloyd; Marjorie M. Walker (Case Reports in Oncological Medicine)
Adult renal rhabdomyosarcoma is a rare subtype of renal sarcoma. We present a case of a renal mass treated with radical nephrectomy that subsequently was shown to be renal rhabdomyosarcoma. We discuss the clinical presentation, imaging findings, and histology for this case and review the available literature.